2017
DOI: 10.1126/scitranslmed.aai8708
|View full text |Cite
|
Sign up to set email alerts
|

Phenome-wide scanning identifies multiple diseases and disease severity phenotypes associated with HLA variants

Abstract: While many phenotypes have been associated with variants in human leukocyte antigen (HLA) genes, the full phenotypic impact of HLA variants across all diseases is unknown. We imputed HLA genomic variation from two populations of 28,839 and 8,431 European ancestry individuals and tested association of HLA variation with 1,368 phenotypes. A total of 104 four-digit and 92 two-digit HLA allele-phenotype associations were significant in both discovery and replication cohorts, the strongest being HLA-DQB1*03:02 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
92
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 105 publications
(98 citation statements)
references
References 64 publications
6
92
0
Order By: Relevance
“…Of all PRS evaluated, the oral cavity/pharyngeal and lung cancer PRS were most commonly implicated in associations with cross-cancer and non-cancer phenotypes. These results support existing evidence of cancer pleiotropy, given that the PRS for both cancers included variants in two well-known pleiotropic cancer regions -TERT-CLPTM1L (2) and HLA (3,4). Notwithstanding shared susceptibility regions, the relationship between oral cavity/pharyngeal and lung cancers was inconsistent.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Of all PRS evaluated, the oral cavity/pharyngeal and lung cancer PRS were most commonly implicated in associations with cross-cancer and non-cancer phenotypes. These results support existing evidence of cancer pleiotropy, given that the PRS for both cancers included variants in two well-known pleiotropic cancer regions -TERT-CLPTM1L (2) and HLA (3,4). Notwithstanding shared susceptibility regions, the relationship between oral cavity/pharyngeal and lung cancers was inconsistent.…”
Section: Discussionsupporting
confidence: 77%
“…Indeed, genome-wide association studies (GWAS) of individual cancer types have identified loci associated with other cancer types, including 5p15 (TERT-CLPTM1L) (2), 6p21 (HLA complex) (3,4), and 8q24 (5). Non-GWAS approaches have yielded further pleiotropic cancer risk variants, and genetic correlation studies have identified cancer pairs with shared heritability (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, prior works indicate that genetic variations within particular MHC genes are known to influence vaccine efficacy (42), rejection rates of transplanted organs (43), susceptibility to autoimmune diseases (44) and antitumor immunity (45,46). Our work raises the possibility that, by altering the maturation and functionality of the immune system, the size of the epitope binding repertoire of MHC variants itself could have an impact on these processes.…”
Section: Discussionmentioning
confidence: 67%
“…2 ). Three of the 11 independent amino acid variations, HLA-DRB1 residue 67 and 71, HLA-DQB1 residue 55 are associated with type 1 diabetes, multiple sclerosis, hypothyroidism, rheumatoid arthritis, and other inflammatory polyarthritis according to PheWAS database 12, 13 . We then estimated to what extent these MHC variants can influence each TRBV gene usage variation using multiple linear regression.…”
Section: Resultsmentioning
confidence: 99%